A new automatic stitching method for full-length lower limb radiography - Alkhatatbeh, Tariq; Wang, Jia Lin; Zhang, Wei Jia; Li, Yong Wei; Xia, Yong; Wang, Wei (Frontiers in Surgery, 2022)
Full-length lower limb X-rays are used to diagnose and plan surgical procedures, such as Total Knee Arthroplasty (TKA) and High Tibial Osteotomy (HTO). Due to the size limitation of digital radiography (DR), panoramic X-ray images cannot be obtained in a single exposure, necessitating multiple exposures and image stitching. In favor of manually constructing full-length X-ray images, we propose a new feature-based automated method for stitching together X-ray images. This new method is based on the Canny algorithm, which detects and aligns bone edges before fusing them using a Wavelet form domain. Twenty-eight sets of lower limb X-ray images obtained from the Second Affiliated Hospital of Xi'an Jiaotong University have been stitched and evaluated. The hip, knee, and ankle (HKA) angle was computed and compared to manually stitched X-ray images by an expert. The stitching time was only three seconds, and the P-value was positive. This method demonstrated greater precision and speed than both manually stitched X-ray images and previously published methods.